THE USE OF INFORMATION TECHNOLOGY METHODS IN TEACHING THE TOPIC "POLYGAMY" - Anuar, A; Kasenov, С.; Rakhmet, Ш.; Baetov, К.; Tleulesova, А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article describes the methods of information technology used in the study of the topic "polyhedra". The introduction provides a brief overview of the effectiveness of using general information technologies in geometry lessons. The types and methods of applying effective means of teaching the topic "polyhedra" of information technology are considered. Further, several examples were shown about the effectiveness of using the GeoGebra program when studying the topic of "polyhedra". In the tasks, the students were given tasks that are difficult to imagine. It has long been known that the correct construction of a drawing in solving geometric problems is half the solution to the problem. The steps of the scheme were recorded and information provided to enable volunteers to complete the following tasks. The effectiveness of the use of information technologies is clearly demonstrated, it is shown that the child develops logical thinking, the ability to imagine. During the lesson, it was considered the possibility of using a mobile phone for effective purposes. Report drawings were presented not only in the form of links, but also in the form of a QR code. It is proved that when studying the topic of "polyhedra" one can easily and interestingly go through the use of effective information technologies. Among information technologies, a list of programs like GeoGebra was given.